Pengaruh Lama Pemaparan Obat Anti Nyamuk Kertas Berbahan Aktif Transfluthrin Terhadap Struktur Histopatologi Pulmo Mencit (Mus musculus L.) - Dewi, Novia Chamala Sari; Sudiastuti, Sudiastuti; Nugroho, Rudy Agung (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2015)
This research aims to determine the effects of long exposure(hours/day) of paper-based active anti mosquito-Transfluthrinon the level of damage and lung histology of mice. CompletelyRandomized Design (CRD) was used in this study. Twentymales mice, 3 months old, average body weight 20 g were usedand divided into 4 groups, viz: K (control), P1 (exposure to 4hours/day), P2 (exposure 8 hours/day), and P3 (exposure 12hours/day). Histological observation of the level of damage hadbeen done through the cell nucleus and the diameter of thealveoli was measured. Data were analyzed by using ANOVAfor diameter alveoli followed by Duncan's Multiple Range Test(DMRT). The results showed that the there was a significantdifference (P <0.05) in the alveolar diameter (P3). Meanwhile,There was also a change in the form of cell undergoing alveolaredema, pyknosis, karyorhesis and kayolisis. This resultsindicated that the paper-based mosquito repellent activeingredient transfluthrin caused several changes in alveoluscells.